2006
DOI: 10.1136/ard.2005.050070
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal manifestations in childhood-onset systemic lupus erythematosus

Abstract: Background: Childhood-onset lupus erythematosus is a rare disorder of unknown origin. Objectives: To describe the frequency of gastrointestinal manifestations at presentation of systemic lupus erythematosus SLE and at follow-up, and discuss the specific causes of these manifestations. Methods: Medical records of 201 patients with childhood-onset SLE followed up in French paediatric nephrological, haematological and rheumatological centres were reviewed and abstracted for gastrointestinal manifestations. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 21 publications
1
72
0
4
Order By: Relevance
“…[24] A more recent study from Northern Ireland did not reveal clinical evidence of SLE among a cohort of 60 celiac disease patients. [25] While gastrointestinal manifestations of SLE are common in both adults and children, [26][27][28] CD is relatively rare among this patient population but should be considered in the setting of malabsorption symptoms. False positive ANA tests may be found in patients with untreated celiac disease.…”
Section: Inflammatory Arthritismentioning
confidence: 99%
“…[24] A more recent study from Northern Ireland did not reveal clinical evidence of SLE among a cohort of 60 celiac disease patients. [25] While gastrointestinal manifestations of SLE are common in both adults and children, [26][27][28] CD is relatively rare among this patient population but should be considered in the setting of malabsorption symptoms. False positive ANA tests may be found in patients with untreated celiac disease.…”
Section: Inflammatory Arthritismentioning
confidence: 99%
“…[13] Pancreatic damage is associated with systemic metabolic diseases, such as diabetic ketoacidosis, systemic lupus erythematosus, Henoch-Schonlein purpura, hemolytic uremic syndrome and others. [9,[14][15][16] L-asparaginase can cause pancreatic dysfunction in children with acute lymphoblastic leukemia (ALL). Pancreatic necrosis is one of the serious adverse effects, and the mortality of this type of pancreatitis is 2.5%.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 SLE-related GI involvement is clinically important because most cases can be lifethreatening and complications are common if not treated promptly. C-reactive protein (CRP) levels are frequently normal or only mildly elevated in cSLE-related abdominal pain 18,[20][21][22] , with the exception of acute pancreatitis in which the CRP is very elevated.…”
Section: Gastrointestinal Manifestationsmentioning
confidence: 99%
“…[23][24][25] Multifocal segments of bowel involvement from multiple vascular territories occur over 90% of the time. 18,19 Inflammatory vasculitis is thought to be due to immune complex deposition, resulting in fibrinoid necrosis of subserosal vessels, leukocytoclasis on the vascular wall, and submucosal edema with diffuse mononuclear cell infiltrate. 26 Several studies have demonstrated that LMV occurs when patients are in the active stage of their disease with elevated SLEDAI or European Consensus Lupus Activity Measure (ECLAM) scores.…”
Section: Lupus Mesenteric Vasculitismentioning
confidence: 99%
See 1 more Smart Citation